The effectiveness of learning through play module on the understanding of number concept among preschool - Zakiah, Mohamad Ashari (2013)
Playing opportunities provided by teachers for pre-school children can help to encourage children’s learning and development process. This study shows that learning through play is very important in children’s learning process. A module of learning through play which focuses on the concept of number was constructed to assist teachers and preschool children in the process of teaching and learning through a planned and systematic way. Piaget and Vygotsky’s theories of cognitive development were the basis of the teaching module in which cooperative play activity was incorporated into cognitive play activity. The effectiveness of the implementation of learning through play module was measured through children's understanding on the concept of number. A quasi-experimental research design using pre and post- tests was applied in this study. Children’s understanding on the number concept was tested twice, before and after the learning process. The teachers in the experimental group used the play module in their teaching of number concept while teachers in the control group used conventional method in teaching the same topic. While children from both groups were found to be homogeneous in the pre-test, outcome from the post test revealed that children in the experimental group significantly outperformed the children in the control group. The findings proved that the usage of learning through play module could significantly increase children’s understanding on the concept of number.